A closer look at the relationships between panic attacks, emergency department visits and non-cardiac chest pain. (May 2019) - Foldes-Busque, Guillaume; Denis, Isabelle; Poitras, Julien; Fleet, Richard P; Archambault, Patrick; Dionne, Clermont E
This study examined the prevalence of emergency department visits prompted by panic attacks in patients with non-cardiac chest pain. A validated structured telephone interview was used to assess panic attacks and their association with the emergency department consultation in 1327 emergency department patients with non-cardiac chest pain. Patients reported at least one panic attack in the past 6 months in 34.5 per cent (95% confidence interval: 32.0%–37.1%) of cases, and 77.1 per cent (95% confidence interval: 73.0%–80.7%) of patients who reported panic attacks had visited the emergency department with non-cardiac chest pain following a panic attack. These results indicate that panic attacks may explain a significant proportion of emergency department visits for non-cardiac chest pain.